Interpretation and diversity of exoplanetary material orbiting white dwarfs. Issue 1 (4th October 2019) - Swan, Andrew; Farihi, Jay; Koester, Detlev; Hollands, Mark; Parsons, Steven; Cauley, P Wilson; Redfield, Seth; Gänsicke, Boris T
ABSTRACT: Nine metal-polluted white dwarfs are observed with medium-resolution optical spectroscopy, where photospheric abundances are determined and interpreted by comparison with Solar system objects. An improved method for making such comparisons is presented, which overcomes potential weaknesses of prior analyses, with numerous sources of error considered to highlight the limitations on interpretation. The stars are inferred to be accreting rocky, volatile-poor asteroidal materials with origins in differentiated bodies, in line with the consensus model. The most heavily polluted star in the sample has 14 metals detected, and appears to be accreting material from a rocky planetesimal, whose composition is mantle-like with a small Fe–Ni core component. Some unusual abundances are present. One star is strongly depleted in Ca, while two others show Na abundances elevated above bulk-Earth abundances; it is speculated that either the latter reflect diversity in the formation conditions of the source material, or they are traces of past accretion events. Another star shows clear signs that accretion ceased around 5 Myr ago, causing Mg to dominate the photospheric abundances, as it has the longest diffusion time of the observed elements. Observing such post-accretion systems allows constraints to be placed on models of the accretion process.